Optimalisasi Regenerasi Dan Pemakaian Kembali Karbon Aktif Untuk Pemungutan Krom Dari Limbah Penyamakan Kulit - Rahayu, Neni; Wintoko, Joko; Hidayat, Muslikhin (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
In the wastewater treatment of leather tanning processes, commercial activated carbon from palm shells is usually used as an adsorbent. Therefore, a study is needed to evaluate the effectiveness of activated carbon that has been repeatedly regenerated and used as a total chromium adsorbent medium in wastewater. This study aims to examine the leaching process that uses acids and bases to analyze the adsorption and regeneration processes of activated carbon. Adsorption time variations of 30 minutes, 60 minutes, 90 minutes, and 120 minutes were used to evaluate how activated carbon interacts with wastewater. Then, the effluent was analyzed by Atomic Absorption Spectrophotometry (AAS) to determine the amount of total chromium remaining in the sample. The activated carbon which had been used as an adsorbent was contacted with 0.1 M H2S04 solution for 4 hours and stirred at 400 rpm using a magnetic stirrer to regenerate the surface of the activated carbon. It is neutralized with an alkaline solution. The Freundlich model is used to determine the value of the adsorption equilibrium constant. After testing 5 times, commercial activated carbon can still be used effectively as a adsorbent medium for total chromium (total Cr) repeatedly. Optimum adsorption contact time was 90 minutes. The optimum absorption efficiency during the fifth stage of the adsorption process was 43.93%.